Acute unilateral vestibular neuritis contributes to alterations in vestibular function modulating circumvention around obstacles: A pilot study suggesting a role for vestibular signals in the spatial perception of orientation during circumvention - Allum, John; Rust, Heiko Mario; Honegger, Flurin (Frontiers in Integrative Neuroscience, 2022)
Background Walking among crowds avoiding colliding with people is described by patients with vestibular disorders as vertigo-inducing. Accurate body motion while circumventing an impeding obstacle in the gait pathway is dependent on an integration of multimodal sensory cues. However, a direct role of vestibular signals in spatial perception of distance or orientation during obstacle circumvention has not been investigated to date. Materials and methods We examined trunk yaw motion during circumvention in patients with acute unilateral vestibular loss (aUVL) and compared their results with age-matched healthy controls (HCs). Subjects performed five gait tasks with eyes open two times: walk 6 m in total, but after 3 m, circumvent to the left or right, as closely as possible, a cylindrical obstacle representing a person, and then veer back to the original path; walk 6 m, but after left and right circumvention at 3 m, veer, respectively, to the right, and left 45 deg; and walk 6 m without circumvention. Trunk yaw angular velocities (YAVs) were measured using a gyroscope system. Results Yaw angular velocity peak amplitudes approaching to, and departing from, the circumvented object were always greater for patients with aUVL compared to HCs, regardless of whether passing was to the aUVLs’ deficit or normal side. The departing peak YAV was always greater, circa 52 and 87%, than the approaching YAV for HCs when going straight and veering 45 deg (p ≤ 0.0006), respectively. For patients with aUVL, departing velocities were marginally greater (12%) than approaching YAVs when going straight (p < 0.05) and were only 40% greater when veering 45 deg (p = 0.05). The differences in departing YAVs resulted in significantly lower trajectory-end yaw angles for veering trials to the deficit side in patients with aUVL (34 vs. 43 degs in HCs). Conclusion The results demonstrate the effects of vestibular loss on yaw velocity control during the three phases of circumvention. First, approaching an obstacle, a greater YAV is found in patients with aUVL. Second, the departing YAV is found to be less than in HCs with respect to the approaching velocity, resulting in larger deficit side passing yaw angles. Third, patients with UVLs show yaw errors returning to the desired trajectory. These results could provide a basis for rehabilitation protocols helping to avoid collisions while walking in crowded spaces.